The impact of distal stress on the spontaneous recovery of conditioned defensive responses - Christopher M. Klinke; Maren D. Lange; Marta Andreatta (Neurobiology of Stress)
Intense and chronic stress strengthens fear memories and increases the risk for mental disorders. Often stressful situations are experienced long before the appearance of the symptoms, but so far, little has been investigated on how distal stress alters fear memories. In a four-day paradigm, 131 healthy individuals were either assigned to the stress-group by means of the socially evaluated cold-pressor test (SECPT) or to the sham-group (control condition). Twenty-four hours later, participants underwent fear acquisition during which two shapes were presented. The first shape (conditioned stimulus, CS+) was associated with an electro-tactile stimulation (unconditioned stimulus, US), whereas the second shape (CS-) were presented alone. During extinction training, both shapes were presented while the US was omitted. To investigate if stress induction alters extinction recall differently depending on the passage of time, participants were tested either one day (recent) or 15 days (remote) after extinction training. Learning was quantified via subjective ratings, startle reflex and skin conductance response. While we found successful acquisition and extinction of the conditioned defensive responses, there was no effect of stress on these learning processes. Stress induction did not alter the spontaneous recovery of the conditioned defensive verbal responses but of the physiological responses as stressed individuals tested two weeks after extinction training showed startle potentiation to CS + vs. CS-. In conclusion, distal stress, even if mild, can strengthen fear memories and weaken extinction memory by the passage of time. This could be a possible mechanism facilitating the onset of stress-related and anxiety disorders.